COVID-19 economic stimulus packages, tourism industry and external debt: The influence of extreme poverty. - Luke Okafor; Usman Khalid (PLoS ONE, 2023)
The COVID-19 outbreak has had a catastrophic effect on the tourism sector and poverty alleviation efforts. This is especially the case, given the crucial role the tourism sector plays in poverty alleviation and the generation of foreign exchange earnings. This study investigates the moderating influence of extreme poverty on the underlying link between the size of the tourism industry and COVID-19 Economic Stimulus Packages (ESPs) while accounting for the influence of external debt. The results show that tourism-dependent economies with a larger share of individuals living in extreme poverty introduced larger ESPs to cushion the impacts of the COVID-19 outbreak. In addition, economies with larger external debt have less fiscal and monetary leeway to alleviate the negative effects of the COVID-19 outbreak.